CONTENT ANALYSIS OF CIGARETTE ADVERTISEMENT IN NEWSPAPER â€˜KEDAULATAN RAKYATâ€™ (1990-2013) - Dyna Herlina Suwarto , Nurhidayati Kusumaningtyas (MTCC, John Hopkins n The Union, 2015)
Cigarette industries are using â€œAdvertisementâ€ as one of their marketing strategies which is a popular strategy to promote a product. Unlike other promotion media, cigarette advertisement not only inform about the product but also create symbol (language and image), values, and message that interpreted by its audience as a part of smoking 'life style' establishment. The research purpose is to understanding how is the information, symbols (language, image), values, message and advertisement strategy that offered by cigarette advertisement to influence audience. Understanding about those factors will contribute to create an effective counter message. This is a textual research using quantitative content analysis by summative data analysis method. The object of the research is cigarette product advertisement that published at newspaper, Kedaulatan Rakyat, during 1990-2013 gathered from Provincial Public library. Research validity will achieve using coding procedure and scheme, enumerator briefing. At the same time, the reliability will accomplish using inter-coder method. The research found that the cigarette advertisements promote some important information: low level of nicotine, the best quality of tobacco and the bestseller cigarette. Moreover, the advertisements were offering symbols that are not related with the product itself. They exhibited images such as animals, vehicles, and household equipments. It is urge to note that the advertisement model dominated by male adult and young. Doing so, it may conclude that the advertisement audience target is male adult and young. Meanwhile the words that publish frequently are popular words, humor, words play, rhyme poems. The manifest values that are delivered related to masculinity, active and happy, special quality of kretek and filter cigarette. The advertisers use message strategy that is set the advertisement to enforce consumer demand by humor and information that are not related to the product itself. Overall the advertisements were developed using transformative approach in order to create brand image and personality product since the product is not has beneficial function for the consumers. So that the research suggests that the health campaign need to involve transformative approach to promote positive feeling among audience about healthy lifestyle without cigarette as the counter message to the cigarette advertisement. Keywords: cigarette advertisement, content analysis, newspaper